2015
DOI: 10.1159/000381143
|View full text |Cite
|
Sign up to set email alerts
|

Positive Direct Immunofluorescence Is of Better Value than ELISA-BP180 and ELISA-BP230 Values for the Prediction of Relapse after Treatment Cessation in Bullous Pemphigoid: A Retrospective Study of 97 Patients

Abstract: Background: ELISA-BP180 values and direct immunofluorescence (DIF) are prognostic factors for relapse after treatment cessation in bullous pemphigoid (BP). Objective: To determine the relevance of ELISA-BP230 antibodies for predicting relapse 6 months after treatment cessation. Methods: We retrospectively selected patients with BP and available data from ELISA-BP180 and -BP230 and DIF performed at treatment cessation. The rate of relapse was calculated at 6 months. We compared ELISA-BP180 and -BP230 values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In BP, like in many other autoimmune diseases, the presence of autoantibodies in serum reflects a failure of tolerance mechanisms on which an inflammatory response may occur . It has been showed that the serum concentration of IgG autoantibodies to BP180 correlated with disease severity and that its fluctuations between days 0, 60 and 150 may predict disease outcome . In this setting, a small decrease in anti‐BP180 IgG serum levels between days 0 and 60 is a factor associated with disease relapse within the first year of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…In BP, like in many other autoimmune diseases, the presence of autoantibodies in serum reflects a failure of tolerance mechanisms on which an inflammatory response may occur . It has been showed that the serum concentration of IgG autoantibodies to BP180 correlated with disease severity and that its fluctuations between days 0, 60 and 150 may predict disease outcome . In this setting, a small decrease in anti‐BP180 IgG serum levels between days 0 and 60 is a factor associated with disease relapse within the first year of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Among BP patients, 73.8-85% were reported to be treated with systemic corticosteroid [15][16][17] and relapse rates were reported to be 15-53%. 3,5,[18][19][20][21][22][23] This clearly contrasts with pemphigus patients; we recently reported that 62% of pemphigus patients experienced relapse at least once and all of them had been treated with oral PSL. 24 In Japanese guidelines for pemphigoid management, oral PSL (0.5-1 mg/kg) is recommended as a first-line treatment for moderate to severe BP.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, 37.2% of patients were treated without oral PSL and the relapse rate was less than 10% in those patients (Tables 1 and 4). Among BP patients, 73.8–85% were reported to be treated with systemic corticosteroid 15–17 and relapse rates were reported to be 15–53% 3,5,18–23 . This clearly contrasts with pemphigus patients; we recently reported that 62% of pemphigus patients experienced relapse at least once and all of them had been treated with oral PSL 24 …”
Section: Discussionmentioning
confidence: 99%
“…High titer of anti-BP180NC16AIgG (>27 IU/mL) is the only factor independently predicting the relapse of BP within one year after discontinuation of treatment, and the positive predictive value and the negative predictive value are 90.9% and 51.2%, respectively ( 19 ). However, in another study, positive DIF was of a better value than BP180 IgG ELISA values for predicting the relapse risk, with 59.0% sensitivity, 78.0% specificity, while 50.0% positive predictive values and 83.3% negative predictive value, respectively ( 20 ). When the ELISA-BP180 value was high or DIF shows positive, treatment to BP should not be ceased.…”
Section: Emerging Biomarkers In Bpmentioning
confidence: 99%